Voodoo River - Crais, Robert (Crais, Robert. Elvis Cole series., 1995)
L.A. private eye Elvis Cole is hired by popular television star Jodie Taylor to delve into her past and identify the biological parents who gave her up for adoption thiry-six years before.. When Cole realizes that his employer knew more than she was telling, Voodoo River becomes a twisting tale of identity, secrets, and murder.